Enhanced mobility preservation of polythiophenes in stretched states utilizing thienyl-ester conjugated side chain. (3rd January 2023) - Yu, Ping-Jui; Lin, Yan-Cheng; Lin, Chia-Yu; Chen, Wen-Chang
Abstract: Recently, diverse approaches to synthesizing intrinsically stretchable conjugated polymers have been presented, such as incorporating the conjugation break spacers or intermolecular interactions in conjugated backbones, resulting in a compromise in the charge carrier mobility. In this study, polythiophenes with flexible [2, 2':5′, 2'':5″, 2‴]-quaterthiophene (QT) or rigid 2-([2, 2′-bithiophen]-5-yl)thieno[3, 2-b]thiophene (BTTT) backbones were engineered with ester- (E−), thienyl- (T-), and thienyl-ester-substituted (TE) side chains for an enriched amorphous content and an improved mechanical tolerance. Polythiophene with QT backbone and TE side chain (PQT-TE) represents the best mobility−stretchability properties evidenced by the polarized UV–vis absorption, grazing incidence X-ray diffraction, and surface morphological analyses. Accordingly, PQT-TE presents a higher chain conformability and crack-onset strain than QT-based polythiophene with T (PQT-T) or E (PDCBT) side chains. This improvement originated from enriched amorphous domains and enhanced backbone planarity using a biaxially extended conjugation design. PQT-TE exhibits high orthogonal mobility preservations of (64, 90)% under 60% strain parallel/perpendicular to the channel direction. Notably, PQT-TE achieves high orthogonal mobility preservations of (48, 65)% after 800 cyclic stretch−release tests under 60% strain, and these improvements are similarly observed in that of BTTT-based polythiophene (PBTTT-TE). This study demonstrates that the jointed design of the biaxial extension and ester functional groups is efficacious in improving the mobility−stretchability properties of polythiophenes. Graphical abstract: Image 1 Highlights: Intrinsically stretchable conjugated polymers with thienyl-ester conjugated side chains. Biaxial conjugation extension and ester functional groups on polythiophenes. Improved chain conformability and crack-onset strain. High orthogonal mobility retentions of 64–90% under 60% strain. High orthogonal mobility retentions of 48–65% after 800 stretch−release cycles.